2000
DOI: 10.1128/iai.68.7.3861-3866.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Brucella abortus Catalase

Abstract: All aerobic organisms have mechanisms that protect against oxidative compounds. Catalase, peroxidase, superoxide dismutase, glutathione, and thioredoxin are widely distributed in many taxa and constitute elements of a nearly ubiquitous antioxidant metabolic strategy. Interestingly, the regulatory mechanisms that control these elements are rather different depending on the nature of the oxidative stress and the organism. Catalase is well documented to play an important role in protecting cells from oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…The position of oxyR is very variable in the different bacterial genomes, but it is often next to a gene involved in oxidative stress protection and regulated by OxyR: for example, ahpC in Mycobacterium tuberculosis (7) and Xanthomonas campestris pv. phaseoli (25), dps in Bacteroides fragilis (32), oxyS in E. coli (4), recG in Pseudomonas aeruginosa (28), kat in B. abortus (17). Similar genomic relationships between oxyR and catalase genes are observed for most members of the Rhizobiales studied so far, such as S. meliloti, Agrobacterium tumefaciens, B. abortus, Mesorhizobium loti, Rhizobium etli, and Rhizobium leguminosarum bv.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The position of oxyR is very variable in the different bacterial genomes, but it is often next to a gene involved in oxidative stress protection and regulated by OxyR: for example, ahpC in Mycobacterium tuberculosis (7) and Xanthomonas campestris pv. phaseoli (25), dps in Bacteroides fragilis (32), oxyS in E. coli (4), recG in Pseudomonas aeruginosa (28), kat in B. abortus (17). Similar genomic relationships between oxyR and catalase genes are observed for most members of the Rhizobiales studied so far, such as S. meliloti, Agrobacterium tumefaciens, B. abortus, Mesorhizobium loti, Rhizobium etli, and Rhizobium leguminosarum bv.…”
mentioning
confidence: 66%
“…The oxyR homologous gene in S. meliloti is located 193 bp upstream of and in the strand opposite to katA. The regulation of an HPII-like catalase by OxyR has been described for Brucella abortus only (17). The alignment of the oxyR-katA intergenic regions from S. meliloti and B. abortus (Fig.…”
mentioning
confidence: 99%
“…Brucella abortus has a single hydroperoxidase, a true catalase, which is expressed in the periplasm (17). In previous studies (10,11), it was shown that Brucella catalase is regulated at the transcriptional level.…”
mentioning
confidence: 99%
“…Although this protein does not possess a standard export signal sequence (63) or a predicted twin arginine transport signal sequence (data not shown), cell fractionation studies with the appropriate controls indicate that this protein resides in the periplasmic compartment (63). B. abortus and Brucella melitensis katE mutants exhibit increased sensitivity to H 2 O 2 compared to their parental strains in in vitro assays (21,33). A B. melitensis katE mutant retains its virulence in experimentally infected goats (21), and B. abortus katE mutants display wild-type virulence in the mouse model (59).…”
mentioning
confidence: 99%